Elucidating the origin of superior electrochemical cycling performance: new insights on sodiation–desodiation mechanism of SnSb from operando spectroscopy. Issue 18 (25th April 2018) - Fehse, Marcus; Sougrati, Moulay T.; Darwiche, Ali; Gabaudan, Vincent; La Fontaine, Camille; Monconduit, Laure; Stievano, Lorenzo
Abstract : As it has been recently shown in the literature, SnSb exhibits better performance in Na-ion than in Li-ion batteries in spite of its even larger volume expansion. Abstract : As it has been recently shown in the literature, SnSb exhibits better performance in Na-ion than in Li-ion batteries in spite of its even larger volume expansion. Where is this special behaviour coming from? In this work, the reversible sodiation–desodiation reaction of SnSb was investigated by simultaneous operando Sn and Sb K-edge X-ray absorption spectroscopy along with operando 119 Sn Mössbauer spectroscopy. Chemometric tools such as principal component analysis and multivariate curve resolution – alternating least squares were used to analyse the whole data sets to gain information on the nature and sequence of formation of different species during electrochemical cycling vs. Na. The obtained results indicate that the sodiation reaction is a two-step process clearly distinct from the reaction of SnSb vs. Li. Firstly Sb is sodiated to form Na3 Sb and an intermediate phase of nanosized metallic Sn, which we were able to identify as α-Sn, commonly unstable at ambient conditions. During the second step, this tin phase is fully sodiated to form Na15 Sn4, as rarely observed for pure Sn-based electrodes. Finally, EXAFS analysis proves that the amorphous SnSb phase formed after one complete cycle is clearly distinct from the pristine material. These new insights on the mechanism of SnSb vs. Na provide a basis for understanding the exceptional electrochemical performance, which is superior not only to SnSb vs. Li but also to Sn vs. Na. The key to the enhanced cycle life and capacity retention lies in the gradual formation of amorphous, nano-confined intermediate phases and correlated elastic softening of highly sodiated tin and antimony phases which have enhanced ability to absorb and mitigate the strong volume changes occurring upon sodiation and desodiation.